Women in “The final meeting” (2009)
Friendship is the main issue in this novel, one of the Hungarian author Sándor Márai’s most remarkable ones; beyond its sheets, a kind of fine-brush painting stands out, in which the features of a true friendship are well-drawn, as well as the strokes tha